1998
DOI: 10.1007/s001670050078
|View full text |Cite
|
Sign up to set email alerts
|

No benefit of bracing on the early outcome after anterior cruciate ligament reconstruction

Abstract: Forty patients were prospectively investigated to evaluate the effects of bandaging after reconstructive surgery of the anterior cruciate ligament (ACL). For the 6 weeks of the postoperative course, the operated knee was bandaged in 20 patients (group A) and braced in the other 20 patients (group B). The isokinetic torque for extension and flexion (Cybex) and the range of motion (ROM) were investigated after 6, 12, 24 and 52 weeks postoperatively. At 24 weeks and 1 year postoperatively the stability of the kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…The quality assessment revealed that 19 studies inadequately described the source population,13 4461 18 studies inadequately reported the preinjury sports participation level of participants,5 12 13 26 46 51 54 57 6170 and 18 studies failed to report the number of participants returning to their preinjury level of sports participation 5 26 44 46 49 55 57 61 62 64 6673…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality assessment revealed that 19 studies inadequately described the source population,13 4461 18 studies inadequately reported the preinjury sports participation level of participants,5 12 13 26 46 51 54 57 6170 and 18 studies failed to report the number of participants returning to their preinjury level of sports participation 5 26 44 46 49 55 57 61 62 64 6673…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies reported mean anterior tibial translation,5 13 44 48 52 55 56 5961 68 71 73 74 7779 with a combined group mean of 1.7 mm side-to-side difference. When the results of the other 20 studies10 4548 50 51 54 58 6265 69 70 8084 were pooled, it was found that 91% of patients had a side-to-side difference in anterior tibial translation of ≤5 mm at final follow-up. Fifteen studies evaluated quadriceps and hamstring strength at final follow-up 13 44 4749 5355 60 62 68 70 72 81 83.…”
Section: Resultsmentioning
confidence: 99%
“…Current study also used elastic bandages, during gait training, which could support the early mobilization with single elbow crutch. [13] A study reported that patients mobilized immediately after ACL reconstruction with the help of elbow crutch for 3 weeks and its result also showed there were no difference between the brace group and no brace group. Also the Lysholm Knee Score and the Tegner Score were improved than the brace group.…”
Section: Discussionmentioning
confidence: 97%
“…[4,13] There is still a lot of controversy concerning the use of braces in rehabilitation following ACL reconstruction. According to surveys in Germany, Australia, and the US, 56.2-85% of surgeons post-operatively prescribe a hard brace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation